Non-progressive Non-immune Hydrops Fetalis Caused by a Novel Mutation in GUSB Gene - Mosallanejad, Asieh; Alaei, Mohammadreza; Ghaffari, Saeed Reza; Rafati, maryam; Saneifard, Hedyeh (Iranian Journal of Child Neurology, 2020)
Mucopolysaccharidosis type VII or Sly syndrome is a rare autosomal recessive disorder caused by deficiency of β Glucuronidase enzyme, which is involved in degradation of glycosaminoglycans. The lack of β Glucuronidase in this lysosomal storage disorder is characterized by various manifestation such as non-immune hydrops fetalis, spinal deformity, organomegaly, multiplex dysostosis, intellectual disability, and eye involvement. It has been found to be caused by a mutation in GUSB gene on chromosome 7 q11. Here we reported an Iranian girl with Mucopolysaccharidosis type VII and a novel mutation (C. 542G>T, P.Arg181Leu) in GUSB gene.